Recloser Installation for Distribution Network Reliability at the Christmas Party - Jefri Ardiansyah; Hamdani Hamdani; Pristisal Wibowo (INFOKUM, 2026)
The reliability of the electricity distribution system is one of the important indicators in assessing the quality of electricity service to customers. The YB.02 feeder located in the working area of ​​PT PLN (Persero) ULP Natal has a network length of 297 km with a total of 11,820 customers and uses a radial network configuration. Disturbances that occur in the downstream area of ​​the feeder have the potential to cause blackouts to a large number of customers, thereby reducing the level of reliability of the distribution system. One of the efforts made to improve network reliability is the installation of Natal Reclosers in Section 8 in the Simpang Pulopadang area. This study aims to analyze the effect of recloser installation on improving the reliability of the distribution network at the YB.02 Feeder. The research method used is a descriptive quantitative method by analyzing disturbance data, the number of affected customers, the duration of blackouts, and the SAIFI and SAIDI reliability indices before and after the recloser installation. The results showed that before the recloser installation, the SAIFI value was 3.30 times/customer/year and the SAIDI was 7.13 hours/customer/year. After the installation of the Natal Recloser, the SAIFI value decreased to 1.12 hours/customer/year and the SAIDI value decreased to 1.02 hours/customer/year. The installation of the recloser was also able to reduce the disturbance area which previously affected around 7,800 customers to around 2,300 customers in the affected section. In addition, the autoreclose function is able to automatically overcome temporary disturbances so that the frequency and duration of blackouts can be minimized. The results showed that the installation of the Natal Recloser was able to reduce the SAIFI value by 66.06% and SAIDI by 85.69%, so it is effective in improving the reliability of the distribution network and continuity of electricity services to customers in the working area of ​​PT PLN (Persero) ULP Natal.